Munyin Tanah Experimental Music | Musik Eksperimental Munyin Tanah - Candana, I Kadek Hari; Muryana, I Ketut (GHURNITA: Jurnal Seni Karawitan, 2024)
Munyin Tanah is an experimental music created to materialize the composer's ideas. This work's creation hopefully provides benefits in the form of new references for musicians and audiences. The method of creation in this work is found in a book by Brewster Ghiselin entitled The Creative Process. Roger Sessions (1952) explains that creating a musical work includes inspiration, conception, and execution. Based on this method, the composer produces experimental musical works by processing musical elements using media that combines non-musical and musical instruments. The musical idea represents sounds that arise from the ground, such as rumbling booming, and sounds produced from the contact of materials made out of soil, such as the sound of rain and earth shifting crust. This is processed through rhythmic integration that explores Balinese gamelan and drumming techniques in Western music, such as single, double, and paradiddle.